2008
DOI: 10.1093/bja/aen128
|View full text |Cite
|
Sign up to set email alerts
|

Volume 100: Case reports: should they be confined to the dustbin?

Abstract: Prolonged low intraoperative BIS TM levels predict increased risk of post-operative mortality: two-year follow-up report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Case reports typically receive few citations, although there are notable exceptions [26]. The number of citations of an article, however, does not necessarily reflect how widely the article has been read or the dissemination of the findings in mainstream media [27]. …”
Section: Impact Factormentioning
confidence: 99%
“…Case reports typically receive few citations, although there are notable exceptions [26]. The number of citations of an article, however, does not necessarily reflect how widely the article has been read or the dissemination of the findings in mainstream media [27]. …”
Section: Impact Factormentioning
confidence: 99%
“…Mahajan and Hunter 13 indicate that case reports/series are often the most commonly read type of article, yet they are rarely among the most cited. Furthermore, Patsopoulos et al 14 suggested case reports have a small impact in heath science literature based on number of times cited.…”
Section: Commentmentioning
confidence: 99%
“…However, using research methodologies such as RCTs that are costly and time intensive often limit scientists and clinicians to examining few variables and subvert the richness of understanding the influences of patient history, individual characteristics, and disease presentation on disease treatment and outcomes. Case reports often shed light on new diseases, anomalous patient variations, unexpected effects of drugs and their forms of administration, and even different approaches to treating common medical conditions in a relatively quick and inexpensive format [6]. …”
Section: Introductionmentioning
confidence: 99%